Role of radio on agricultural development: A review - Khanal, Shree Ram (Bodhi: An Interdisciplinary Journal, 2013)
This article discusses the role of radio in agricultural development of Nepal. The work is based on the review of some selected texts. The author’s main position here is that Nepal's present radio boom bears a high scope for a significant role in the promotion of agriculture, and that discoursing this issue should get due importance since Nepalese economy is highly dependent on agricultural products. Bodhi: An Interdisciplinary Journal, 5, 2011, Page 201-206 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8054